2004
DOI: 10.1073/pnas.0403888101
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cancer DNA phenotype prior to tumor formation

Abstract: Using the carcinogen 3-methylcholanthrene (MCA), we demonstrate with Fourier transform-infrared spectroscopy that a cancer DNA phenotype is produced well in advance of palpable tumors. We further demonstrate that the administration of cyclophosphamide markedly inhibits the development of the cancer phenotype and concomitantly delays tumor formation. MCA, injected into the hind legs of mice, produced a variety of significant structural changes in the nucleotide bases and phosphodiester-deoxyribose backbone, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 27 publications
(40 reference statements)
1
41
0
Order By: Relevance
“…This phenotype was identified in normal tissues 8 weeks before tumor formation. Strikingly, administration of the prodrug cyclophosphamide every 10 days after 3-methylcholanthrene injection delayed tumor formation by about 30% and almost completely suppressed development of the phenotype, thus suggesting that it may also be inhibited by other intervention strategies with less toxic side effects (4).…”
Section: U Sing Established Fourier Transform-infrared (Ft-ir) Statis-mentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype was identified in normal tissues 8 weeks before tumor formation. Strikingly, administration of the prodrug cyclophosphamide every 10 days after 3-methylcholanthrene injection delayed tumor formation by about 30% and almost completely suppressed development of the phenotype, thus suggesting that it may also be inhibited by other intervention strategies with less toxic side effects (4).…”
Section: U Sing Established Fourier Transform-infrared (Ft-ir) Statis-mentioning
confidence: 99%
“…tical models (1)(2)(3)(4)(5), we have demonstrated previously a cancer DNA phenotype in the limbs of mice 10 weeks after injecting the carcinogen 3-methylcholanthrene (4). This phenotype was identified in normal tissues 8 weeks before tumor formation.…”
Section: U Sing Established Fourier Transform-infrared (Ft-ir) Statis-mentioning
confidence: 99%
“…The DNA samples were also grouped by lesion concentrations, which revealed an uneven distribution of age relative to increasing values. In addition, we used Fourier transform-infrared (FT-IR) spectroscopy 5,[20][21][22] to delineate structural differences in the stromal DNA in relation to the various age groups and to determine whether such differences exist between the matched cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Mourant et al demonstrated that the ratio RNA/lipid could be used to determine the proliferative status of mammalian cells [13]. A diagnostic advantage of the FT-IR spectroscopy in cancer research is that the development of a cancer DNA phenotype can be observed prior to the tumor formation, notably for prostate carcinomas [11]. As tumorigenesis in humans is a multistep process, cells acquire several capabilities leading to the progressive conversion of normal human cells into cancer cells, notably the limitless potential of growth [8].…”
Section: Resultsmentioning
confidence: 99%